Bone densitometry and calcium serum levels in chickens treated with filtered or unfiltered water - Amoroso, L [UNESP]; Baraldi, Asm [UNESP]; Barreiro, Fr [UNESP]; Pacheco, Mr [UNESP]; Alva, Jcr [UNESP]; Soares, Nm; Pacheco, Lg [UNESP]; Melaré, Mc [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2013)
The aim of this study was to evaluate whether the drinking water of the School of Agricultural and Veterinary Sciences, UNESP, Jaboticabal, Brazil, affected bone mineral density and serum calcium levels of 14-, 21-, and 45-day-old broilers. Bone mineral density (BMD) of the tibiae was assessed using optical densitometry radiographic technique and serum calcium levels. Tibial BMD increased as broilers aged, and achieved its peak at 45 days of age. It was higher in the distal epiphysis of the birds that ingested filtered water (p<0.05) compared with those supplied with unfiltered water. Therefore, it is concluded that filtered water promoted better bone quality in relative to those ingested unfiltered water.
Keywords: Bone mineral density; Broilers; serum calcium levels; tibia; Water quality